Efficacy, safety and pharmacokinetics of subcutaneous azacitidine in Chinese patients with higher risk myelodysplastic syndromes: Results from a multicenter, single‐arm, open‐label phase 2 study. Issue 3 (28th December 2017) - Du, Xin; Lai, Yue‐Yun; Xiao, Zhijian; Liu, Ting; Hu, Yu; Sun, Aining; Li, Xiao; Shen, Zhi‐Xiang; Jin, Jie; Yu, Li; Laille, Eric; Dong, Qian; et al.
Abstract: Background: Azacitidine safety and efficacy were established in studies of mainly Caucasian patients. Differences in drug metabolism enzymes between Caucasian and East Asian populations prevent extrapolation of drug effects between these groups. This phase 2 study evaluated azacitidine safety, efficacy and pharmacokinetics in patients with higher‐risk myelodysplastic syndromes (HR‐MDS) in mainland China. Methods: Patients aged ≥18 years with HR‐MDS were to receive subcutaneous azacitidine 75 mg/m 2 /day for 7 days per 28‐day cycle, for ≥6 cycles. Pharmacokinetic blood samples were collected in cycle 1 predose on days 5–7, and postdose on day 7. Pharmacokinetic outcomes are descriptively compared with those of a historical North American cohort. Results: Of 72 participants, 46 (64%) completed ≥6 cycles. Response rate was 96%, driven primarily by stable disease (94%); one patient achieved complete remission. Hematologic improvement was attained by 53% of patients. Azacitidine mean plasma concentration versus time profiles were similar in shape for Chinese ( n = 12) and North American ( n = 45) patients. Maximum plasma concentration ( C max ) was higher in Chinese patients; however, mean azacitidine exposure (1190 ng·h/mL) was similar to the North American cohort (1021 ng·h/mL). Most common grade 3–4 treatment‐emergent adverse events (TEAEs) were thrombocytopenia (69%) and neutropenia (67%). Conclusions: Azacitidine was safe and effective in Chinese patients with HR‐MDS. Clinical outcomes were comparable to those for primarily Caucasian patients in the phase 3 AZA‐001 study. C max differences between Chinese and North American patients were not associated with differences in TEAE frequency or severity. No initial azacitidine dose adjustment is required for Chinese patients with HR‐MDS.